BUDAYA KERJA GURU MADRASAH TSANAWIYAH DI KABUPATEN WAY KANAN - Suwanto, Suwanto (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2018)
Work culture is a set of behavioral patterns that areinherent in every individual in an organization. Buildingculture means also improving and maintaining thepositive side, and trying to familiarize certain behavioralpatterns to create new, better forms. This research wasconducted to see how the work culture (integrity,professionalism, innovation, responsibility andexemplary teacher of Islamic Islamic Madrasah in WayKanan District. Based on the results of the study, it wasobtained a picture that the five cultural values wereimplemented well even though the results were notmaximized. This cultural value has a positive impact,both on the internal (including educators and educationpersonnel) and external impacts including thecommunity, as evidenced by the increasing performanceof educators and community services.The barriers tothe application of cultural values are caused by: a) lackof communication ) limited human resources in thefield of technology c) low understanding of the stateapparatus against the applicable rules.